Review on QBD Approaches to HPLC Method Development and Validation on Tirzepatide - Ravina Mule; Dr Vinayak Gaware (Asian Journal of Pharmaceutical Research and Development, 2026)
Tirzepatide, a novel dual GIP and GLP-1 receptor agonist, requires highly sensitive and robust analytical methods for quality control. This study describes a systematic Quality by Design (QbD) approach for the development and validation of a stability-indicating RP-HPLC method. The Analytical Target Profile (ATP) was defined to ensure a short runtime with high resolution. Critical Quality Attributes (CQAs), including the tailing factor (T ≤ 1.5) and resolution (Rs > 2.0), were monitored against Critical Method Parameters (CMPs) such as mobile phase composition (Acetonitrile percentage), flow rate, and buffer pH. Using a Central Composite Design (CCD), the design space was established to identify the Method Operable Design Region (MODR). Forced degradation studies under acidic, alkaline, and oxidative conditions confirmed the method’s stability-indicating nature, as degradants were well-resolved from the Tirzepatide peak. The results indicate that the proposed QbD-based method is cost-effective, robust, and highly suitable for routine pharmaceutical analysis.